1993
DOI: 10.1083/jcb.123.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Exofacial epitope-tagged glucose transporter chimeras reveal COOH-terminal sequences governing cellular localization.

Abstract: Abstract. The insulin-regulated adipocyte/skeletal muscle glucose transporter (GLUT4) displays a characteristic steady-state intracellular localization under basal conditions, whereas the erythrocyte/brain transporter isoform (GLUTI) distributes mostly to the cell surface. To identify possible structural elements in these transporter proteins that determine their cellular localization, GLUT1/GLUT4 chimera eDNA constructs that contain the hemagglutinin epitope YPYDVPDYA (HA) in their major exofacial loops were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 32 publications
6
62
1
Order By: Relevance
“…This observation extends, therefore, recent results showing the presence of Daxx in the cytoplasm (2, 14 -16). The punctate staining of the cytoplasm of 3T3-L1 fibroblasts and 3T3-L1 adipocytes incubated with antibodies against Daxx agrees with the localization of Daxx in LDM, the cellular fraction that enriched in endosomes contains a sizable part of GLUT4 (30). The localization of Daxx to endosomes and the identification of endosomes carrying ligand-receptor complexes as the sites where signal transduction is often initiated (31) suggests that the interaction of Daxx with proteins such as Fas receptor T␤RII could also occur at endosomes.…”
Section: Discussionmentioning
confidence: 63%
“…This observation extends, therefore, recent results showing the presence of Daxx in the cytoplasm (2, 14 -16). The punctate staining of the cytoplasm of 3T3-L1 fibroblasts and 3T3-L1 adipocytes incubated with antibodies against Daxx agrees with the localization of Daxx in LDM, the cellular fraction that enriched in endosomes contains a sizable part of GLUT4 (30). The localization of Daxx to endosomes and the identification of endosomes carrying ligand-receptor complexes as the sites where signal transduction is often initiated (31) suggests that the interaction of Daxx with proteins such as Fas receptor T␤RII could also occur at endosomes.…”
Section: Discussionmentioning
confidence: 63%
“…The chimeric transporter 4HB1, which contains the NH2-terminal 183 amino acids of GLUT4, also showed some intracellular localization in NIH3T3 and 3T3-L1 fibroblasts (43; and Fig. 3), though other investigators have found this chimeric transporter located primarily at the cell surface in COS cells and Xenopus oocytes (11,27). In 3T3-L1 adipocytes, the chimeric transporter 4HB1 was detected primarily in intracellular compartments in the basal state, and only slightly redistributed to the cell surface in response to insulin (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental strategies based on the construction of chimeric transporter proteins have led to identification of several structural domains implicated as critical to the intracellular sequestration of GLUT4 (11,27,29,30,43). However, a major limitation of the previous studies has been that none of the cells into which the transporters have been introduced represents a physiologically meaningful model system as defined by two criteria: expression of significant quantities of the endogenous GLUT4 glucose transporter and an insulin-stimulatable augmentation in hexose uptake comparable to the in vivo target tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing the coverslips were mounted in 90% glycerol containing 2.5% diazabicyclo[2.2.2]octane. To examine Myc-GLUT4-EGFP translocation in adipocytes transfected with plasmid DNAs, cells were washed, fixed, and immunostained with a set of antibodies using procedure described previously (36). Briefly, first the cell surface Myc-GLUT4-GFP was detected with anti-myc monoclonal antibody and rhodamine B-labeled goat anti-mouse IgG.…”
Section: Methodsmentioning
confidence: 99%